Palmitoylation of the feline immunodeficiency virus envelope glycoprotein and its effect on fusion activity and envelope incorporation into virions - Gonzalez, Silvia Adriana (2012)
The feline immunodeficiency virus (FIV) envelope glycoprotein (Env) possesses a short cytoplasmic domain of 53 amino acids containing four highly conserved cysteines at Env positions 804, 811, 815 and 848. Since palmitoylation of transmembrane proteins occurs at or near the membrane anchor, we investigated whether cysteines 804, 811 and 815 are acylated and analyzed the relevance of these residues for Env functions. Replacement of cysteines 804, 811 and 815 individually or in combination by serine residues resulted in Env glycoproteins that were efficiently expressed and processed. However, mutations C804S and C811S reduced Env fusogenicity by 93% and 84%, respectively, compared with wild-type Env. By contrast, mutant C815S exhibited a fusogenic capacity representing 50% of the wild-type value. Remarkably, the double mutation C804S/C811S abrogated both Env fusion activity and Env incorporation into virions. Finally, by means of Click chemistry assays we demonstrated that the four FIV Env cytoplasmic cysteines are palmitoylated.